Monitoring equity in the delivery of health services: a Delphi process to select healthcare equity indicators - Clement P. Buclin; Moreno Doninelli; Laura Bertini; Patrick Bodenmann; Stéphane Cullati; Arnaud Chiolero; Adriana Degiorgi; Armin Gemperli; Olivier Hugli; Anne Jachmann; Yves Jackson; Joachim Marti; et al. (Swiss Medical Weekly)
AIMS OF THE STUDY: Health equity is a key component of quality of care and an objective for a growing number of quality improvement projects for deontological, ethical, public health and economic reasons. To monitor equity in the delivery of health services in Switzerland, there is a need to implement valid, measurable and actionable equity indicators, along with vulnerability stratifiers such as migrant status, which could lead to differences in quality of care. The aim of this study was to develop a set of healthcare equity indicators and stratifiers targeting inpatient and outpatient populations and to test their feasibility.